2021
DOI: 10.1111/ijd.15815
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopy, dermoscopy, and histopathology features of atypical intraepidermal melanocytic proliferations associated with evolution to melanoma in situ

Abstract: Background Atypical intraepidermal melanocytic proliferations (AIMP) is a descriptive term sometimes applied to biopsies that do not fulfill diagnostic criteria of melanoma. They are common on sun-damaged skin, but their definition and management are controversial.Objective To describe dermoscopic (DS), reflectance confocal microscopic (RCM) and histopathological features of AIMP and identify features associated with subsequent melanoma in situ (MIS). Methods A retrospective analysis of AIMP lesions correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The main features used to differentiate between LM and AIMP both histologically and on RCM are the confluence and location of atypical melanocytes (Rocha et al, 2022). In LM, these are present at all levels of the epidermis; however, in AIMP, whilst the melanocytes are enlarged, there is no pagetoid spread, and they are present only in basal layers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main features used to differentiate between LM and AIMP both histologically and on RCM are the confluence and location of atypical melanocytes (Rocha et al, 2022). In LM, these are present at all levels of the epidermis; however, in AIMP, whilst the melanocytes are enlarged, there is no pagetoid spread, and they are present only in basal layers.…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing between AIMP and LM is important as AIMP may only require ongoing monitoring while LM usually requires some form of definitive treatment before it may progress to invasion and possibility of metastasis (lentigo maligna melanoma). AIMP, in contrast to LM, can continue to be monitored in vivo and tends not to respond to topical or radiotherapy treatments (Rocha et al, 2022). Thus, correct diagnosis determines the level of treatment required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that most lesions currently reported as naevi with atypical intraepidermal melanocytic proliferation (AIMP) are, in fact, benign, and that their significance lies in the potential pitfall for overdiagnosis of malignant melanoma. However, this pilot study included AN in the malignant category, since studies have shown that up to 20% of these lesions are diagnosed as melanoma in situ (MIS) in pathology revisions ( 28 ). Furthermore, it has been demonstrated previously in a retrospective study that the risk of evolution to MIS in AIMP lesions is higher in lesions that demonstrate a high number of dendritic cells touching each other in RCM images ( 28 ).…”
Section: Methodsmentioning
confidence: 99%